The Non-Objective World 1914-1955. - Staber, Margit; University Art Museum - The University of Texas, Austin (London : Annely Juda Fine Art, 1973)
Agam, Yaacov ; Albers, Josef ; Andreenko, Michel ; Annenkov, Georges ; Arp, Hans (Jean) ; Baertling, Olle ; Baljeu, Joost ; Bauer, Rudolf ; Beothy, Etienne ; Bergmann-Michel, Ella ; Biederman, Charles ; Bill, Max ; Bolotowsky, Ilya ; Bortnyik, Sándor ; Buchheister, Carl ; Buchholz, Erich ; Burchartz, Max ; Cahn, Marcelle ; Calder, Alexander ; Charchoune, Serge ; Delaunay, Robert ; Delaunay, Sonia ; Dexel, Walter ; Diller, Burgyone ; van Doesburg, Theo ; Domela, César ; Elliott, Ronnie ; Exter, Alexandra ; Fleischmann, Adolf Richard ; Flocon, Albert ; Freundlich, Otto ; Gabo, Naum ; Glarner, Fritz ; Gleizes, Albert ; Gorin, Jean ; Graeser, Camille ; Hélion, Jean ; Hepworth, Barbara ; Herbin, Auguste ; Hill, Anthony ; Hinterreiter, Hans ; Huszar, Vilmos ; Kandinsky, Wassily ; Kassak, Lajos ; Kliun, Ivan ; Klucis, Gustavs ; Koudriachov, Ivan ; Kupka, Frantisek ; Laloy, Yves ; van der Leck, Bart ; Lissitzky, El ; Loewensberg, Verena ; Lohse, Richard ; Maatsch, Tilo ; Magnelli, Alberto ; Malevich, Kasimir ; Martin, Kenneth ; Martin, Mary ; Michel, Robert ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moore, Henry ; Nicholson, Ben ; Nouveau, Henri ; Pasmore, Victor ; Péri, László ; Pevsner, Antoine ; Popova, Liubov ; Puni, Ivan ; Reggiani, Mauro ; Reichel, Hans ; Rickey, George ; Rodchenko, Alexander ; Röhl, Karl Peter ; Rothschild, Judith ; Schreyer, Lothar ; Schwitters, Kurt ; Servranckx, Victor ; Soldati, Atanasio ; Stazewski, Henryk ; Suetin, Nikolay ; Taeuber-Arp, Sophie ; Tutundjian, Leon ; Valmier, Georges ; Vantongerloo, Georges ; Vasarely, Victor ; Vezelay, Paule ; Vordemberge-Gildewart, Friedrich ; Wiegand, Charmion Von
biog. per kunstenaar
Duits & Engels
The Non-Objective World 1914-1955, Annely Juda Fine Art, London, July 5th - September 22nd 1973 ; University Art Museum - The University of Texas at Austin, October 14th - December 15th 1973
boek